Yield response and pathological characterization of promising genotypes of soybean against major diseases in Madhya Pradesh: YIELD RESPONSE AND PATHOLOGICAL CHARACTERIZATION OF SOYBEAN AGAINST MAJOR DISEASES - PAWAN K AMRATE; M K SHRIVASTAVA (Journal of Oilseeds Research, 2021)
The yield potential along with multiple disease resistance in 38 promising soybean genotypes including four checks i.e. JS 20-34, JS 335, JS 20-98 and NRC 86 was assessed under field condition of JNKVV, Jabalpur which is one of the hot spot locations for major diseases of soybean like Charcoal rot, Aerial blight and Yellow mosaic. Significant differences were observed for days to 50 per cent flowering, days to maturity, yield (kg/h) and 100 seed weight. The highest yield was obtained from JS 21-72 (2650 kg/h) followed by Himso 1689 (2255 kg/h) and JS 21-71 (2222 kg/h). Maximum 100 seed weight of 14.37g was recorded in JS 21-72 followed by JS 21-71 (14.2g) and JS 20-34 (14.16g). Out of thirty eight, the yield ofseven genotypes i.e. Himso 1688, MAUS 734, DSb 33, NRC 139, SL 1171, VLS 97 and BAUS 100 could not be recorded due to complete mortality of the plants by charcoal rot. Eight genotypes viz., JS 21-71, MACS 1566, JS 21-72, DS 3110, MACS 1620, JS 20-34(C), RSC 11-15 and Himso 1689 against charcoal rot, seven genotypes against aerial blight, eighteen genotypes against YMV and thirty-three (33) against bacterial pustule disease showed high resistance. Overall, three genotypes viz., JS 21-71, JS 21-72 and Himso 1689 exhibited absolute tomoderate resistance against charcoal rot plus absolute/highresistance to YMV, RAB and bacterial pustule.